Degradation of 2,4-dinitrophenol by two Rhodococcus erythropolis strains, HL 24-1 and HL 24-2. - Lenke, H (1992)
Two Rhodococcus erythropolis strains, HL 24-1 and HL 24-2, were isolated from soil and river water by their abilities to utilize 2,4-dinitrophenol (0.5 mM) as the sole source of nitrogen. Although succinate was supplied as a carbon and energy source during selection, both isolates could utilize 2,4-dinitrophenol also as the sole source of carbon. Both strains metabolized 2,4-dinitrophenol under concomitant liberation of stoichiometric amounts of nitrite and 4,6-dinitrohexanoate as a minor dead-end metabolite.